Effects of Online Teaching Model of “Super Star Learning System and QQ Group” on Learning Enthusiasm and Academic Performance - Li, Bowen; Yu, Wentao; Jiang, Jianming; Zhang, Yixin; Zhao, Jingshan (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Online teaching based on multiple platforms has become an important and respected teaching method. Aim: We aimed to investigate effect of “Super Star Learning System and QQ Group” online teaching model on learning enthusiasm and academic performance. Materials and Methods: An evaluation system of learning enthusiasm was established and evaluated. Students’ academic performance in online teaching group and traditional teaching group were compared. Nine variables were selected, including chapter learning times (1), chapter quiz score (2), homework score (3), classroom interaction score (4), usual performance (5), classroom performance score (6), classroom practice score (7), rush answer score (8) and discussion replies score (9). Correlation between learning enthusiasm and academic performance was investigated, and important variables were obtained by principal component regression analysis. A questionnaire was used to find important factors affecting students’ satisfaction. Results: Academic performance of online teaching group was improved to a medium degree in comparison with traditional teaching group (p <0.001). Some variables (variable 2,4,5,6) from learning enthusiasm were moderately correlated with academic performance (r2 =0.608, r4 =0.514, r5=0.604, r6 =0.516, p <0.01). The order of influencing variables on academic performance was variable 2,3,5,9,4,6,7,8,1. Mean scores of achievement expectation factor and learning experience factor were 4.24 (± 0.73) and 4.23 (± 0.76), respectively. Conclusion: The online teaching model could stimulate learning enthusiasm and improve academic performance of pharmacy students. There was a certain positive correlation between learning enthusiasm and academic performance. Achievement expectation and learning experience might be the two most important factors that affect students’ satisfaction
Keywords: Online teaching model; Learning enthusiasm; Academic performance; Super; star learning system and QQ group; Satisfaction survey